Grief Of Families Left Behind By Family Members Due To Covide-19 In Semarang - Sri Endang Windiarti; Ahmad Riyadi; Umi Margi Rahayu; Annisa Muliani Tangdilintin (Publikasi Indonesia, 2023)
Background: Grieving is a response that arises as a result of an individual experiencing one of which is loss. Not only the grieving phase which includes denial, anger, bargaining, depression, acceptance which describes the condition of grieving but there is also a grieving response which includes cognitive, emotional, behavioral and physiological responses where these responses can be different in each individual, because humans are unique creatures, researchers use observational interview techniques in conducting this study, to find out the grieving response to one person and another. Objective: This study aims to determine the picture of grieving family members left behind by their families due to COVID-19 in Semarang Regency. Method: Qualitative descriptive research design with data analysis using Collaizi method. Results: the description of the participants' grieving response showed the results of cognitive responses including denial and acceptance, emotional: depression, anger, gaining, acceptance. Behavioral: depression, then on physiological responses: depression, gaining, acceptance. Conclusion: the grieving phase was irregular, but all four participants had similar cognitive, emotional, behavioral, physiological responses.